Influencer Marketing and Consumer Engagement: The Role of Food Experts in Shaping Attitudes Towards Organic Products - Nikoletta Kallioupi, Rafailia; Strigas, Athanassios; J. Vliamos, Spyros (British Journal of Marketing Studies, 2024)
The Covid-19 pandemic has spurred a consumer trend toward embracing healthier lifestyles and diets. Leveraging primary studies centered on influencer marketing and its influence on consumer behavior, this study aims to scrutinize and evaluate the effect of Food Expert Influencers on consumers' attitudes towards organic products. Our conceptual model, utilizing the theory of social comparison, contributes to formulating hypotheses based on which specific characteristics of Food Expert Influencers are capable of influencing and impacting consumer behavior towards organic foods. On the basis of survey data collected from 306 respondents, structural equation modeling was employed to test our hypotheses and measure the proposed conceptual model. The results indicated that influencers' sexual orientation, appealing lifestyle, specialized knowledge in a particular domain, personal traits like beauty or sex appeal, and their follower count exert a considerable influence on consumer behavior, notably fostering positive attitudes towards organic products. These findings hold substantial theoretical implications, offering crucial insights for marketing strategies in the organic food products sector, as well as for corporate social responsibility. They underscore the importance of carefully selecting influencers who resonate with the target demographics and can forge authentic connections with them. Moreover, the results suggest that harnessing the credibility of Food Experts of Influence (FEIs) can influence consumer behavior and potentially bolster the sales of organic products.